MAIL ARCHIVE SYSTEM MODEL USING ADVANTAGE DATABASE SERVER (ADS) - Manulangga, Gloria Christina; Bataona, Daniel Silli; Laumal, Folkes Eduard (Universitas Negeri Malang, 2018)
Computerization process in archiving activity is completely needed and already many kinds of archiving model application. One of those models is Advantage Database Server (ADS) that support table system and data access based on SQL. This model is also flexible and easy to apply on institution infrastructure. This research aims to prove that the model can improve the productivity of an institution on archiving activity. The development method used is a prototype with user acceptance system testing. The result shows that there are average time reduction of about 50.8% on data saving, 95.1% on data searching, and 93.9% on report printing.